Optimization of Solid Phase Extraction Using Chelating Disk for Cr(III) and Fe(III) Concentration in Water Samples by ICP-AES Analysis - Anandieka Maya Talitha; Zainab El-Dahshan; Abd-El Aal (Journal of Chemical Learning Innovation, 2026)
Purpose of the study: This study aims to optimize the solid phase extraction method using a chelating disk for the concentration of Cr(III) and Fe(III) metals in water samples, determine the optimum concentration conditions, evaluate the percent recovery, and examine the effect of the presence of alkali and alkaline earth metal matrices on the effectiveness of separation and analysis using ICP-AES. Methodology: The study used an experimental method with solid-phase extraction based on 3M Empore Chelating Disk chelating disks, Varian 720 ES ICP-AES instrument analysis, Eppendorf micropipettes, InoLab pH meters, and OHAUS analytical balances. Standard chemicals from Merck were used for solution preparation. The stages included sample preparation, pH optimization and HNO3 concentration, recovery test, RAL statistical analysis, F test, and BNT test. Main Findings: The optimum concentration condition was obtained at pH 5.5 with HNO3 concentration of 2 M. The recovery percentage of Cr(III) reached 98.9% and Fe(III) was 99.1%. The concentration test showed a recovery of 97–100% at various concentrations and sample volumes. In the matrix test, the recovery of Cr(III) and Fe(III) was 99.0% and 99.6%, respectively, while alkali and alkaline earth ions showed low recovery so they did not interfere with the adsorption process of the target metal. Novelty/Originality of this study: This research provides new insights into the selectivity of chelating disks under complex matrix conditions and expands the application of solid-phase extraction for more efficient and accurate ICP-AES-based trace metal analysis.